An operations research approach to the triple jump - Brimberg, J.; Hurley, B.; Ladany, S. P. (International Journal of Sport Management and Marketing, 2006)
There are wide-ranging views among track and field experts regarding the optimal strategy to use in the triple jump. The controversy pertains to the effort which should be expended in each of the hop, step, and jump phases. In this paper, we develop a dynamic programming approach for finding the optimal strategy. The results of our model support a recent shift in opinion in favour of a jump-dominated technique. However, the improvement is marginal, and hence, the best strategy may in the end be athlete specific.